Controlling institutions : international organizations and the global economy / Randall W. Stone. - Stone, Randall W., 1966- (Cambridge University Press, 2011)
How is the United States able to control the IMF with only 17 per cent of the votes? How are the rules of the global economy made? This book shows how a combination of formal and informal rules explains how international organizations really work. Randall W. Stone argues that formal rules apply in ordinary times, while informal power allows leading states to exert control when the stakes are high. International organizations are therefore best understood as equilibrium outcomes that balance the power and interests of the leading state and the member countries. Presenting a new model of institutional design and comparing the IMF, WTO, and EU, Stone argues that institutional variations reflect the distribution of power and interests. He shows that US interests influence the size, terms, and enforcement of IMF programs, and new data, archival documents, and interviews reveal the shortcomings of IMF programs in Mexico, Russia, Korea, Indonesia, and Argentina.